Intra-arterial cocktail therapy for patients with anterior circulation large vessel occlusion who achieved endovascular reperfusion - Zhao, Zi-Ai; Hu, Hai-Zhou; Li, Wei; Qiu, Jing; Zhao, Yong-Gang; Nguyen, Thanh N.; Chen, Hui-Sheng (Frontiers in Neurology, 2024)
BackgroundClinically ineffective reperfusion (CIR) refers to the discrepancy between successful reperfusion and a favorable functional outcome in patients with large vessel occlusion (LVO) stroke after endovascular treatment (EVT). The Improving Neuroprotective Strategy for Ischemic Stroke with Sufficient Recanalization after Thrombectomy by Intra-arterial Cocktail Therapy (INSIST-CT) trial aimed to explore the safety, feasibility, and efficacy of intra-arterial cocktail therapy using argatroban, dexamethasone, and edaravone in patients who achieved sufficient reperfusion after EVT.MethodsIn this prospective, single-arm, pilot study, eligible patients with anterior circulation LVO who achieved sufficient reperfusion after EVT were enrolled in the INSIST-CT trial. Consecutive patients who met the inclusion/exclusion criteria were included in the control group retrospectively. In the INSIST-CT group, argatroban, dexamethasone, and edaravone were continuously administered for 30 min into the culprit artery after sufficient recanalization. The primary endpoint was the proportion of favorable functional outcome, defined as a modified Rankin Scale (mRS) score of 0–2 at 90 days. The primary safety outcome was symptomatic intracranial hemorrhage (sICH). Propensity score matching (PSM) and inverse probability of treatment weighting (IPTW) analyses were performed to account for multiple confounders.ResultsA total of 30 patients were included in the INSIST-CT group, and 261 patients were included in the control group. The proportion of the patients with the primary endpoint was 60% in the INSIST-CT group and 55.9% in the control group (unadjusted odds ratio [OR] 1.18, 95% CI 0.55–2.61, p = 0.67; adjusted OR 1.42, 95% CI 0.62–3.26, p = 0.41). No significant difference in sICH at 48 h after treatment was observed between the two groups (unadjusted OR 0.96, 95% CI 0.15–3.56, p = 0.96; adjusted OR 0.82 95% CI 0.17–3.97, p = 0.809). Similar results were observed after the PSM and IPTW analyses.ConclusionIn anterior circulation, LVO patients who achieved sufficient reperfusion after EVT, bridging intra-arterial cocktail therapy with argatroban, dexamethasone, and edaravone may be safe and feasible. However, it did not improve the 90-day functional outcomes. A numerically higher probability of a favorable outcome in the INSIST-CT group suggests the potential promise of this cocktail therapy in reducing clinically ineffective reperfusion.Clinical trial registrationClinicalTrials.gov, NCT04202549.